TOOLS FOR REGULATING MARKETS OF AGRICULTURAL PRODUCTS IN CONDITIONS OF ECONOMIC UNCERTAINTY (INNOVATIVE ECONOMY, 2021)
Horlachuk M.A. TOOLS FOR REGULATING MARKETS OF AGRICULTURAL PRODUCTS IN CONDITIONS OF ECONOMIC UNCERTAINTYPurpose. The aim of the article is theoretical and methodological substantiation of tools for regulating markets of agricultural products in conditions of economic uncertainty and possible models of their application in strategically important agricultural markets.Methodology of research. The theoretical and methodological basis of the study is scientific positions that are reflected in the works of Ukrainian and foreign scientists. The following methods were used to achieve this goal: abstract and logical - to generalize the methods of regulation and diagnosis of the current state of research on the regulation of agricultural markets; inductions and deductions - to identify relationships in the process of grouping regulatory tools; epistemological and dialectical methods - to identify the most common problems of market regulation in conditions of uncertainty.Findings. The key problems of regulation of agricultural markets in the modern period are generalized and systematized. Based on this, the tools and methods of market regulation are analysed. The factors that determine the application of various methods and tools of market regulation in conditions of economic uncertainty are studied. Perspective directions of development of the organized market of agricultural products are considered.Originality. The market mechanism of regulation of agricultural production in relation to the specifics of agricultural markets is assessed, and the main methods of application of special market regulation tools are systematized, which allowed to substantiate the model of beef market development in Ukraine (by forming a cattle exchange and introducing an integrated quality system).Practical value. The results of the study can be a theoretical and methodological basis for the introduction of a specialized commodity market for agricultural products in Ukraine, as well as the subject of further research to address fundamental problems of agricultural markets in conditions of economic uncertainty, which will eliminate or reduce business risks.Key words: agricultural market, organized market of agricultural products, stock market, market regulation tools, economic uncertainty.
Keywords: Key words; agricultural market; organized market of agricultural products; stock market; market regulation tools; economic uncertainty.